2006
DOI: 10.1093/jhered/esl020
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of 37 Breed-Specific Single-Nucleotide Polymorphisms in Sheep

Abstract: We identified 37 single-nucleotide polymorphisms (SNPs) in sheep and screened 16 individuals from 8 different sheep breeds selected throughout Europe. Population genetic measures based on the genotyping of about 30 sheep from the same 8 breeds are reported. To date, there are no sheep SNPs documented in the National Center for Biotechnology Information dbSNP database. Therefore, the markers presented here contribute significantly to those currently available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 21 publications
2
13
0
1
Order By: Relevance
“…This finding is in agreement with results obtained for other European sheep breeds (Geriotti et al 2004). The second pattern, variant T, as described by Geriotti et al (2004) and Pariset et al (2006), occurred either with a decreased frequency of 10% to 36% in the Italian sheep population and elsewhere in the European population or, as in the present study, was not found.…”
Section: Resultssupporting
confidence: 61%
“…This finding is in agreement with results obtained for other European sheep breeds (Geriotti et al 2004). The second pattern, variant T, as described by Geriotti et al (2004) and Pariset et al (2006), occurred either with a decreased frequency of 10% to 36% in the Italian sheep population and elsewhere in the European population or, as in the present study, was not found.…”
Section: Resultssupporting
confidence: 61%
“…Large scale European studies by the Econogene Consortium and others [13][16] involved some UK breeds, including the Exmoor Horn and Welsh Mountain shown subsequently to be geographically concentrated [8]. Isolated Scottish Island populations have also been studied in global surveys, including the numerically scarce breed of the Soay, and those in the Hebrides, Faeroe and Orkney [15], [17]–[19].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, a nucleotide change C/T was detected in Baluchi sheep breed at nt 271 of IGF -1 gene. The same mutation (in IGF -1 gene) has been detected in 8 different sheep breeds selected throughout Europe (Pariset et al, 2006) and in three Italian dairy sheep (Scata et al, 2010). These researchers found that allele T exerted a positive effect on maintaining a constant milk yield level during lactation.…”
Section: Discussionmentioning
confidence: 64%